Activity in vitro of ten antimicrobial agents against Neisseria gonorrhoeae. A study of the correlation between the sensitivities. Issue 5 (October 1976) - Meheus, A; Piot, P; Pattyn, S; van Dyck, E; van den Berghe, D
Abstract : 105 Belgian strains of Neisseria gonorrhoeae were tested for their sensitivity to penicillin, ampicillin, rifampicin, erythromycin, tetracycline, streptomycin, spectinomycin, sulphamethoxazole, trimethroprim, and a combination of sulphamethoxazole and trimethroprim in a 5:1 ratio. Distribution and median values of minimum inhibitory concentrations (MICs) are given and discussed. 42 per cent. of strains were relatively resistant to penicillin (MIC greater than or equal to 0-04 mug/ml.), but only 2 per cent. showed high-level resistance (MIC greater than or equal to 0-38 mug/ml.), which is comparable with the prevalence of decreased sensitivity found in other European countries. A significant positive correlation (P less than or equal to 0-01, rank correlation coefficient) is found between the sensitivities to penicillin, ampicillin, erythromycin, tetracycline, and streptomycin, except for the ampicillin-erythromycin and ampicillin-tetracycline pairs. Rifampicin is correlated with tetracycline. No correlation is found between the sensitivities to spectinomycin and any of the other drugs. The combination of sulphamethoxazole and trimethoprim in a 5:1 ratio also shows a significant positive correlation with penicillin and ampicillin and with sulphamethoxazole and trimethoprim separately.